The Influence of Supervision and Employee Competence on The Discipline of Performance Report Resolution at The Provincial Education Office of South Sumatra. - Aisyah, Siti; Wulandari, Novita; Abduh, Muhammad (Universitas Medan Area, 2025)
This study aims to identify the impact of supervision and employee competence on the level of discipline in completing performance reports at the Education Office of South Sumatra Province. Adequate supervision improves employee discipline by 39.9%, while employee competence contributes 65.6% to reporting discipline. The research method used in this study is a quantitative approach with a survey technique. Data was collected through questionnaires distributed to the Education Office of South Sumatra Province employees. Multiple regression analysis was used to test the relationship between supervision, employee competence, and discipline in completing performance reporting. The study's findings indicate that good supervision has a significant positive effect on reporting discipline, and the same applies to employee competence, which plays a key role in improving discipline. Based on the results of this study, it is recommended that the Education Office of South Sumatra Province strengthen its supervision system and optimize training programs for employees to improve discipline in performance reporting.